PENGEMBANGAN DAYA TARIK WISATA BERBASIS MASYARAKAT DI PANTAI VATUVOU, DISTRIK LIQUISA, TIMOR LESTE - Santos Guterres, Cipriana Dos (Jurnal Master Pariwisata (JUMPA), 2014)
Vatuvou beach, located in the Village Vatuvou, Liquica District      of East Timor, has the potential to be developed into a tourist attraction, but until now its potential has not fully developed yet. The aim of this study is to determine the potential of Vatuvou Beach, to know how the local community have been involved to develop Vatuvou beach, to formulate the most effective strategies to develop it has a community based tourist attraction. The results of this study indicated that Vatuvou coastal region could be used as a tourist attraction in the District of Liquisa, because it has the existing potential such as beach panorama with sunset, black sandy beaches and under–sea wealth, availability of facilities and infrastructure to support tourism, such as water, electricity, road, telecommunication, public toilets, parking, and accommodation (but still limited). Socio-cultural potential as hospitality of the people in the village of Vatuvou, traditional activities, such as handcrafted, and rituals performed by people in the village of Vatuvou. In addition, the strategic location of the Vatuvou beach easily leads to some nearby tourist attraction, such as lake Maubara, Maubara Fort, historical buildings of Portuguese’s heritage, and souvenir center. The involvement of community participation in the coastal development of Vatuvou has been through the initial proceses, namely planning stage, development and evaluation of activities that have been implemented. Through the description, it can be concluded that the strategy of tourism development of Vatuvou beach can be made by the following procedures (1) Increasing the quality and quantity of human resources in tourism, (2) Inviting foreign or local investors to the potential of the existing tourism sectors, (3) Developing the potential of cultural as tourist attractions, and (4) Improving tourism facilities and infrastructure to support tourism activities in Vatuvou coastal areas.